Structural conditions for currency internationalisation: International finance and the survival constraint - Stefan Angrick (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
This paper examines the relationship between currency internationalisation and economic structure. It argues that the hierarchical and asymmetric architecture of the international monetary system imposes a "survival constraint" upon non-centre countries that obliges them to generate net inflows of the international centre currency to finance their payment commitments. It outlines why management of this constraint has historically been associated with a development approach that prioritises exports and investment over domestic consumption. It is demonstrated how this development approach creates an economic structure that is subject to path dependence and network effects, which perpetuates the role of non-centre countries as users of the international currency and the role of centre countries as suppliers of the international currency. It is argued that currency internationalisation cannot be pursued in isolation of broader economic policy, but rather requires economic structural change, political mediation, and accommodative international economic structures. Specifically, raising the international profile of the Chinese renminbi requires rebalancing of the Chinese economy towards domestic demand, whereas the status of the US dollar is intimately intertwined with the international openness of the US economy.
Keywords: F02; F1; F33; F63; 330; international currency; international monetary system; economic structure; economic development; liquidity flows; survival constraint